Cellular recruitment in myocardial ischaemia/reperfusion injury. (June 2016) - Bonaventura, Aldo; Montecucco, Fabrizio; Dallegri, Franco
Abstract: Background: Myocardial infarction (MI) is strictly linked to atherosclerosis. Beyond the mechanical narrowing of coronary vessels lumen, during MI a great burden of inflammation is carried out. One of the crucial events is represented by the ischaemia/reperfusion injury, a complex event involving inflammatory cells (such as neutrophils, platelets, monocytes/macrophages, lymphocytes and mast cells) and key activating signals (such as cytokines, chemokines and growth factors). Cardiac repair following myocardial infarction is dependent on a finely regulated response involving a sequential recruitment and the clearance of different subsets of inflammatory cells. Materials and methods: This narrative review was based on the works detected on PubMed and MEDLINE up to November 2015. Results: Infarct healing classically follows three overlapping phases: the inflammatory phase, in which the innate immune pathways are activated and inflammatory leucocytes are recruited in order to clear the wound from dead cells; the proliferative phase, characterized by the suppression of pro‐inflammatory signalling and infiltration of 'repairing' cells secreting matrix proteins in the injured area; and the maturation phase, which is associated with the quiescence and the elimination of the reparative cells together with cross‐linking of the matrix. All these phases are timely regulated by the production of soluble mediators, such as cytokines, chemokines and growth factors. Conclusion: Targeting inflammatory cell recruitment early during reperfusion and healing might be promising to selectively inhibit injury and favour repair. This approach might substantially improve adverse postischaemic left ventricle remodelling, characterized by dilation, hypertrophy of viable segments and progressive dysfunction.